Борьба с ностальгией как поэтический прием в поздней лирике Марины Цветаевой - Войтехович, Роман (Studia Rossica Posnaniensia, 2019)
Tsvetaeva spent seventeen years in exile and could not avoid the topic of nostalgia. However, her solution of the theme is polemical against the dominant tendencies in emigrant literature. Instead of aspiration to return to a concrete place, to the unchangeable organization of life (prerevolutionary Russia), she forges baroque-romantic type of nostalgia as a desire for eternal movement following a mobile target (after Charles Baudelaire).